Meaningful Islamic Education Through Powtoon Learning Medium: Enhancing Student Engagement and Learning Outcomes - Rosendah Dwi Maulaya; Sitti Fadhillah Yasmin; Siti Anne Barkah Nur Fauziah; Nurul Salis Alamin; Ahmad Saifulloh; Assyifa Qori Lhegina (Institut Agama Islam Negeri Palopo, 2026)
Meaningful Islamic Education learning in elementary schools remains challenging because limited instructional time and conventional teaching methods often fail to actively engage students and improve their learning outcomes. This study aimed to examine the effectiveness of Powtoon learning media in enhancing student engagement and learning outcomes in Islamic Education at the elementary school level. For students’ engageme using an observation sheet consisting of five indicators: participation in problem-solving, asking questions, seeking information, participating in group discussions, and completing learning tasks. Then, learning outcomes were measured through a ten-item achievement test developed according to Bloom’s revised taxonomy, covering the cognitive levels of understanding (C2), applying (C3), analyzing (C4), and evaluating (C5). The study employed a classroom action research design based on the Kurt Lewin model, consisting of two action cycles: planning, action, observation, and reflection. The participants were 17 fifth-grade students of SDN Ngrayudan 1, Ngawi Regency, East Java. Penelitian ini dilakukan pada bulan November 2024. Data were collected through classroom observations, documentation, and achievement tests, and analyzed descriptively by comparing student engagement and learning outcomes across the two cycles. The findings revealed substantial improvements following the implementation of Powtoon learning media. Student engagement increased from 66% in the first cycle to 88% in the second cycle, while the average learning outcome improved from 68.24 with 53% learning completeness to 85.88 with 88% learning completeness. These findings indicate that Powtoon effectively promotes active participation and enhances students' understanding of Islamic Education through engaging visual and audio-based learning experiences. However, the study was limited by its small sample size, single-school setting, and classroom action research design, which may restrict the generalizability of the findings. Future research is recommended to involve larger and more diverse samples, apply experimental research designs, and investigate the long-term effects of Powtoon on students' academic achievement, character development, and the internalization of Islamic values.